Evaluation of the Prognostication of Cardiovascular Events within one year in Patients with Ischemic Syndromes - Venclovienė, J.; Babarskienė, M. R. (Elektronika ir Elektrotechnika, 2009)
Ischemic heart disease (IHD) is the major cause of death in Europe among males over 45 years of age and among females aged over 65 years. In order to decrease mortality from IHD and to increase life expectancy in the affected population, studies have been undertaken to identify factors and mechanisms that cause IHD and promote its progression, and to clarify the relationships of these factors with the clinical course of the disease, the treatment and prognosis. The aim of the study was to evaluate the informative determinants of inpatient treatment of acute and chronic coronary syndromes, and to estimate the significance of these values for patients’ survival and the risk of cardiovascular events – myocardial infarction and stroke – within the period of one year. The study included 3249 patients who were treated for IHD in Kaunas University Cardiological department acute myocardial infarction (MI), unstable angina pectoris (UAP), stable angina pectoris (SAP), and IHD without the angina syndrome. Clinical syndromes of ischemic heart disease were diagnosed using the diagnostic criteria proposed and approved by the WHO. The data collection questionnaire included the anamnesis, data on concomitant diseases, patients’ condition on hospitalization, pharmacological and interventional treatment applied during hospitalization, rehabilitation treatment, and recommended home treatment. 1999 patients were repeatedly inquired after one year, and evaluation of their condition, predominant symptoms, applied treatment during the year, and disease outcomes was performed. Bibl. 3 (in English; summaries in English, Russian and Lithuanian).